Show, tell and re-enact: The reason why the earliest followers of Jesus found the Eucharist meaningful - Groenewald, Jonanda (HTS teologiese studies, 2011)
The purpose of this article has been to examine how the earliest followers of Jesus experienced the Eucharist. What was their reason for participating in the Eucharist? What kind of value did this rite add to their lives? What was the meaning attached to it? In the end, this approach might assist us to gain a deeper understanding of this ‘early Christian’ rite, which, in turn, could help us to comprehend what kind of value the Eucharist could add to our lives today.